If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + -2x) = 14x (1 * -7 + -2x * -7) = 14x (-7 + 14x) = 14x Add '-14x' to each side of the equation. -7 + 14x + -14x = 14x + -14x Combine like terms: 14x + -14x = 0 -7 + 0 = 14x + -14x -7 = 14x + -14x Combine like terms: 14x + -14x = 0 -7 = 0 Solving -7 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x+-11y=45.5 | | -7x-8=-60 | | 8=4c+1 | | 9w=32+w | | -7x-6+9x=-4 | | -8(-1+4p)=-5(6p-1)+1 | | 41x-3+20x=180 | | x+y(-11)=45.5 | | 1x+17+2x=7+x | | -3-(1-7A)= | | 41x+3+20x=180 | | 43+x=59 | | 6(1+3)=-8(-2+5)-4 | | 82x+9=-99+82x | | 40n^3+48n^2+5n+6= | | 6(5-2x)-2x=86 | | 4z^2+52z=0 | | 18p+90= | | 4x+472=9 | | 3x-[(2x+5)-2(x+3)]+4+x^2=(x+3)(x-5) | | -18=7k+2k | | 17-20x=(-13-5x).4 | | 110+3x-8+3x+6=102 | | 2(m-5)x+2=0 | | 9[w+8]=-7w-24 | | -29=-4x-3(-2x+15) | | 8(j+5)=6 | | 1(x+2)=-3x | | 0+y=11 | | 6g-(g-7)=132 | | -9x-19=-199 | | 23x=60x |